Mechanisms of thyrotropin receptor-mediated phenotype variability deciphered by gene mutations and M453T-knockin model - Makkonen Kristiina; Jännäri Meeri; Crisostomo Luis; Kuusi Matilda; Patyra Konrad; Melnyk Vladyslav; Linnossuo Veli; Ojala Johanna; Ravi Rowmika; Löf Christoffer; Makela Juho-Antti; Miettinen Paivi; et al. (American Society for Clinical Investigation, 2025)
The clinical spectrum of thyrotropin receptor-mediated (TSHR-mediated) diseases varies from loss -of -function mutations causing congenital hypothyroidism to constitutively active mutations (CAMs) leading to nonautoimmune hyperthyroidism (NAH). Variation at the TSHR locus has also been associated with altered lipid and bone metabolism and autoimmune thyroid diseases. However, the extrathyroidal roles of TSHR and the mechanisms underlying phenotypic variability among TSHR-mediated diseases remain unclear. Here we identified and characterized TSHR variants and factors involved in phenotypic variability in different patient cohorts, the FinnGen database, and a mouse model. TSHR CAMs were found in all 16 patients with NAH, with 1 CAM in an unexpected location in the extracellular leucine-rich repeat domain (p.S237N) and another in the transmembrane domain (p.I640V) in 2 families with distinct hyperthyroid phenotypes. In addition, screening of the FinnGen database revealed rare functional variants as well as distinct common noncoding TSHR SNPs significantly associated with thyroid phenotypes, but there was no other significant association between TSHR variants and more than 2,000 nonthyroid disease endpoints. Finally, our TSHR M453T-knockin model revealed that the phenotype was dependent on the mutation's signaling properties and was ameliorated by increased iodine intake. In summary, our data show that TSHR-mediated disease risk can be modified by variants at the TSHR locus both inside and outside the coding region as well as by altered TSHR-signaling and dietary iodine, supporting the need for personalized treatment strategies.